DEVELOPING 4C – BASED HOTS ASSESSMENT TO IMPROVE STUDENTS’ CRITICAL THINKING SKILLS AT GRADE VI ELEMENTARY SCHOOLS IN KUDUS DISTRICTS - Tigas Tri Kurniawan; Santoso; Sri Utaminingsih (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study investigated the development, characteristics, and effectiveness of a 4C-based Higher Order Thinking Skills (HOTS) assessment in enhancing sixth-grade students’ critical thinking abilities in mathematics learning at elementary schools in Kudus. Specifically, the objectives were: (1) to formulate a 4C-based HOTS assessment design aimed at improving students’ critical thinking skills; (2) to describe the defining characteristics of the developed 4C-based HOTS assessment; and (3) to analyze its effectiveness in improving students’ critical thinking abilities. The research employed a Research and Development (R&D) approach by adapting the Borg and Gall development model, which consists of ten systematic stages. The field trial involved 73 sixth-grade students, comprising 37 students from SD 1 and SD 2 Gribig as the experimental group and 36 students from SD 1 and SD 3 Klumpit as the control group. Data were collected through observation, questionnaires, tests, and interviews. To determine effectiveness, data were analyzed using gain score analysis and t-tests at a significance level of 0.05. The results indicated that the developed HOTS assessment based on the 4C framework possessed seven main characteristics: (1) measuring higher-order thinking skills, (2) promoting divergent thinking, (3) utilizing multiple representations, (4) incorporating contextual and problem-based situations, (5) applying varied questioning techniques, (6) assessing communication skills, and (7) evaluating collaboration skills. Statistical analysis demonstrated that the 4C-based HOTS assessment was effective in improving students’ critical thinking abilities and learning outcomes. This was evidenced by an increase in the average critical thinking score of the experimental group to 80.59, categorized as moderate, and an increase in the average learning outcome score to 89.05, also within the moderate category. In conclusion, the implementation of a 4C-based HOTS assessment significantly enhanced sixth-grade students’ critical thinking abilities in mathematics learning at elementary schools in Kudus, thereby supporting the integration of 21st-century skills within assessment practices.